Fabricación de bloques de tierra comprimida con adición de residuos de construcción y demolición como reemplazo del agregado pétreo convencional (2014)
The present article suggests an alternative that contributes to give a step towards the continuos cycle of Recycling-Fabrication-Use-Recycling from considering the possibility of understating debris as a raw material for new processes, thus reducing the extraction of materials -- To that end this article suggests the fabrication of compressed earth blocks from the use of the resulting earth from construction and demolition (C&D) debris as aggregates, this way substituting the use of traditional aggregates completely -- Blocks with RCD addition comply with the physical and mechanical specifications established by the Colombian technical standard